PERFORMANCE IMPROVEMENT OF AN AIR-CONDITIONING SYSTEM DURING REFRIGERANT EVAPORATION - Hamed Alhamdo, Mohammed; Abdulwahed Theeb, Maathe; Jaber Abdulhameed, Jaafar (Journal of Engineering and Sustainable Development, 2018)
In hot weather countries, the temperature and pressure of the air-conditioning system are increased considerably. This causes a decrease in the cooling capacity of the cycle and also causes an increase in power consumption. In this work, an experimental and theoretical investigation has been done to improve the evaporator outlet fluid temperature. Engineering Equation Solver (EES) software has been used to analyze the performance of the experimental data. For this purpose, several ranges of evaporator water flow rates are considered tested. The amount of water flow rate is varied with respect to the evaporator load. The results indicate that the increase of water flow rate (160 to 190) L/h causes an increase of COP by (11.1 %). The outlet cooling temperature from the evaporator has been found to reduce by about (11.3%). However, the (170 L/h) flow rate of water has been found as the best rate for improving evaporator temperature.